Determination of phytoplankton community structure and biomass with HPLC-CHEMTAX and microscopic methods during winter and summer in the Qinzhou Bay of the Beibu Gulf - Pan, Huizhu; Xu, Mingben; Lan, Caibi; Ma, Jixian; Li, Jie; Lu, Jiachang; Lai, Junxiang (Frontiers in Marine Science, 2023)
The Qinzhou Bay, a typical semi-enclosed bay, is facing environmental pressure from local fast-growing industrial and aquacultural development. Dominant species of phytoplankton community (based on microscopic examination) show a trend of miniaturization, while pico-phytoplankton (based on CHEMTAX analysis) is widely distributed in Qinzhou Bay. However, most previous investigations of phytoplankton community based on microscopic method that undetected small-sized cell (< 3 μm), and limited by scarce studies on CHEMTAX analysis, the long-term dynamic data of small-size phytoplankton are lacking in Qinzhou Bay. It is recognized that combining microscopic examination with CHEMTAX analysis could provide a good taxonomic reliability for large cells and valuable information about small-size groups. In this study, microscopic examination and High Performance Liquid Chromatography (HPLC)-CHEMTAX analysis were employed to characterize the spatiotemporal variability of the phytoplankton community structure in Qinzhou Bay in winter and summer of 2021. The results of microscopic observations showed that the phytoplankton community was characterized by diatoms and dinoflagellates mainly. Diatoms dominated in both seasons, of which Skeletonema costatum bloom occurred in the summer. CHEMTAX analysis not only agreed well with microscopy data for diatoms and dinoflagellates, but also helped identification of other small-sized flagellates and cyanobacteria that hard to observe by microscope. The results of CHEMTAX analysis found that diatoms, prasinophytes and cryptophytes co-dominated the total chlorophyll a in winter while diatoms became the dominant group in summer. In addition, our results indicate that the proportion of small-sized flagellates has increased in the past decade in Qinzhou Bay, especially for cryptophytes. Temperature, nutrient availability, and selective grazing of oyster affected the succession of phytoplankton community from co-dominance of diatoms and flagellates in winter to absolute diatoms dominance in summer. The distribution of prasinophytes and cryptophytes on a spatial scale were related to the location of shellfish culture area and estuary, respectively, rather than by nutrients. Eutrophication, selective grazing of oyster and warming were the driving factors of long-term changes in phytoplankton composition in Qinzhou Bay. This study enhanced our understanding of entire phytoplankton community dynamics and its relationship with environmental factors in Qinzhou Bay.